Toward Preventive Maintenance and Rehabilitation of Bridges in Cameroon - SEBA MINSILI, Lezin; Michel MBESSA, Michel; PETTANG, Crispin; DAMANDI TARANG, Nadia (European Journal of Sustainable Development, 2015)
Most bridges in Cameroon built in postcolonial period are more than fifty years old and are in dilapidated structural state. This situation was caused by the inadequacy of trained technical experts and of required maintenance programs that were tributary to the scarcity of limited financial means. Since a bridge has a prescribed lifespan with decreasing structural capacities, we must guarantee its safe function using appropriate inspection and monitoring methods. This paper outlines some aspects of research and development related to ongoing bridge curative and preventive maintenance in the country. The proposed methodology expresses the bridge reliability index as a functional value of its bearing capacity. Results, obtained through application of the methodology on local bridges, show that it is possible to extend the bridge lifespan for more than thirty years if appropriate curative and predictive maintenance works are done in due time. Technical officials in the Country presently are seeking means to implement these findings to the national bridges network. Keywords: bridge maintenance, monitoring, reliability index, corrosion, fatigue, repair.